The effect of early mother-infant skin to skin contact and suckling on duration of exclusive breastfeeding: a Randomized Controlled Trial - Paranon Limrattamorn; Kasemsis Kaewkiattikun (The Royal Thai College of Obstetricians and Gynaecologists, 2013)
Objective:To compare duration of exclusive breastfeeding of mothers who contact and suckling with their child within 30 minutes postpartum, with mothers who contact and suckling with their child after 30 minutes postpartum.Materials and Methods: Fifty term pregnant women who had normal labor for their first child at the department Obstetric and Gynecology were chosen to participate in this study. Simple random sampling method was used to assign participants into early contact and suckling group and late contact and suckling group. Data were collected from telephone interview monthly from 1-6 months postpartum.Results: There were initially 50 participants involved in the study, 4 participants were not included due to loss contaction. The remaining 26 participants (56.5%) were in the early contact and suckling group and 20 participants (43.5%) were in the late contact and suckling group. At the first month of postpartum, 100% of mothers breastfed in both groups. The percentages of exclusive breast feeding decreased in each month from 1-6 months postpartum in both groups of participants. There was no statistically different in exclusive breastfeeding in each month between two groups (p=0.481, 0.151, 0.300, 0.603 and 0.492 from 2-6 months of postpartum.)Conclusion: No statistically significant different in rate and duration of exclusive breastfeeding between early contact and suckling group and late contact and suckling group.